Computer and computing technologies in agriculture IV 4th IFIP TC 12 conference, CCTA 2010, Nanchang, China, October 22-25, 2010, selected papers, part III - Li, Daoliang; Liu, Yande; Chen, Yingyi (IFIP advances in information and communication technology, 2011)
This book constitutes Part II of the refereed four-volume post-conference proceedings of the 4th IFIP TC 12 International Conference on Computer and Computing Technologies in Agriculture, CCTA 2010, held in Nanchang, China, in October 2010. The 352 revised papers presented were carefully selected from numerous submissions. They cover a wide range of interesting theories and applications of information technology in agriculture, including simulation models and decision-support systems for agricultural production, agricultural product quality testing, traceability and e-commerce technology, the application of information and communication technology in agriculture, and universal information service technology and service systems development in rural areas.